An exploration of Food Forward SA’s impact on the South African food waste market economy. - Khambule, Esethu (The IIE, 2022)
The purpose of this research was to explore the link between Food Forward SA and food waste in order to determine the extent to which Food Forward SA can be considered a meaningful brand. However, with limited information linking Food Forward SA to food waste, it was difficult to determine the extent to which Food Forward can be considered a meaningful brand. In light of this, the study aimed to explore how the contributions of this organisation impacted the social, economic and environmental communities they operate in in order to determine if they are an effective long term solution. As a result, a limited sample of industry professionals were interviewed and allowed for a general overview of the state of the industry. 5 semi-structured (30 - 45 minute) interviews were conducted to obtain direct data. The purpose of the interviews were to help find key insights into the relationship Food Forward SA has with its donor/beneficiary organisations as well as to gain a holistic view on their impact in the industry. The findings reflect that the core question of this study, to what extent can food forward be considered a meaningful brand, is slightly nuanced. On the one hand, from a capitalist perspective, the brand can be understood as a holistic brand. On the other hand, a holistic view of the industry reflects that the brand can only be considered meaningful to a limited extent. This is due to the fact that the Food Banks are an unsustainable band aid solution to mitigating food loss and food insecurity. This is because food banks aim “to meet the needs of the green economy” (Warshawsky, 2018: 4) and the government, along with business owners, purposely create scarcity to maintain the market price. As a result their existence prevents people from having access to food- making it unsustainable. At the same time, the main incentive of the existence of food banks is to maintain food market prices. Therefore their primary goal is profit driven.Thus, Food Forward SA can be understood to be a meaningful brand to a limited extent due to the issues explored above.
Keywords: Waste management; Meaningful brands; Food banks; Economy